2011
DOI: 10.1002/elps.201000484
|View full text |Cite
|
Sign up to set email alerts
|

In‐line coupling SPE and CE for DNA preconcentration and separation

Abstract: An in-line SPE method coupled to CE was developed for the analysis of DNA. The amino silica monolith was prepared in situ by polymerization of tetraethoxysilane and N-(β-aminoethyl)-γ-aminopropyltriethoxysilane in ethanol aqueous solution at the inlet end of a 100 μm id fused-silica capillary, and the remaining part of the capillary was used as separation channel. The procedure for this in-line SPE-CE method was constructed on the basis of investigation on operational conditions such as the introduction mode o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…6. It indicated that the concentration was magnified near 5 times in 10 s. Compared to in-line preconcentration method 11 (100 times in 40 min) and on-chip polymerase chain reaction (PCR) 27 (40 cycles in 108 min), the proposed method is quick enough to increase DNA concentration for analytic and detection purpose. It is noted that the preconcentration of DNA in this high conductive solution is achieved by p-DEP.…”
Section: -6mentioning
confidence: 99%
See 1 more Smart Citation
“…6. It indicated that the concentration was magnified near 5 times in 10 s. Compared to in-line preconcentration method 11 (100 times in 40 min) and on-chip polymerase chain reaction (PCR) 27 (40 cycles in 108 min), the proposed method is quick enough to increase DNA concentration for analytic and detection purpose. It is noted that the preconcentration of DNA in this high conductive solution is achieved by p-DEP.…”
Section: -6mentioning
confidence: 99%
“…However, it is too specific for DNA molecules with a certain length due to its fixed pore size. Chemical method, 10,11 based on absorption and desorption processes, is another conventional way to enhance DNA concentration, prior to capillary electrophoresis (EP). Electrical method is the most popular technique due to its simple implementation and reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Among systems that have been applied to human body fluids, that described by Feng et al. is noteworthy. They constructed “in situ” an amino silica monolithic column that was applied to develop a method for the sensitive analysis of DNA fragments.…”
Section: Analysis Of Human Fluids Collected By Noninvasive Methodsmentioning
confidence: 99%
“…The pre‐concentration factor of about 250‐fold was obtained in the 2 h fully automated process. Feng et al combined SPE with CE for the separation of DNA fragments by CSE . An amino silica monolith, prepared in situ by polymerisation of tetraethoxy‐silane and N ‐(β‐aminoethyl)‐γ‐aminopropyltriethoxysilane in EtOH at the inlet of the capillary was used as the SPE column.…”
Section: Extractionmentioning
confidence: 99%